PENERAPAN POLA PENGEMBANGAN KEMAHASISWAAN DI PTM - Effendy, Muhadjir (Jurnal Bestari, 1993)
The two main affairs in every university are academic affairs ans student affairs. No gap between them. They strengthen and tighten each other. University will have a good achievement and prestige when these two pillars are combined harmoniously. Here is fundamental existence of student. To educate a good student, university needs a good framework of his affairs. Muhammadiyah Universities (Perguruan Tinggi Muhammadiyah/PTM) can be considered as